Palm Farmers' Strategies In Increasing Income Reviewed From Post Transformation Maqashid Syariah - Ridho Erianto; Marliyah, Marliyah; Zuhrinal M. Nawawi (Dinasti Publisher, 2024)
This research aims to find out the main priority strategies for oil palm farmers in increasing income in terms of post-transformation sharia maqashid in Labuhanbatu district, North Sumatra province by presenting the internal and external conditions that have been carried out so far which have been discussed with relevant experts. The method in this research uses a qualitative approach with SWOT analysis and the QSPM method. This research used questionnaires and interviews with 10 respondents divided into 5 SWOT respondents and 5 QSPM respondents. From the results of the SWOT analysis, it can be ascertained that the strategy obtained after processing it in the IFAS and EFAS matrices is a progressive strategy. This strategy means that you can maximize your strengths and take advantage of opportunities. Furthermore, the QSPM analysis showed that the main priority strategy that must be implemented is strategy number 2 with a TAS value of 5.565, namely the role of agricultural instructors is maximized so that farmers' knowledge and abilities increase and they can work well.